Genome Analysis of Thermosulfurimonas dismutans, the First Thermophilic Sulfur-Disproportionating Bacterium of the Phylum Thermodesulfobacteria - Mardanov, Andrey V.; Beletsky, Alexey V.; Kadnikov, Vitaly V.; Slobodkin, Alexander I.; Ravin, Nikolai V. (Frontiers in Microbiology, 2016)
Thermosulfurimonas dismutans S95T, isolated from a deep-sea hydrothermal vent is the first bacterium of the phylum Thermodesulfobacteria reported to grow by the disproportionation of elemental sulfur, sulfite, or thiosulfate with carbon dioxide as the sole carbon source. In contrast to its phylogenetically close relatives, which are dissimilatory sulfate-reducers, T. dismutans is unable to grow by sulfate respiration. The features of this organism and its 2,1 Mb draft genome sequence are described in this report. Genome analysis revealed that the T. dismutans genome contains the set of genes for dissimilatory sulfate reduction including ATP sulfurylase, the AprA and B subunits of adenosine-5′-phosphosulfate reductase, and dissimilatory sulfite reductase. The oxidation of elemental sulfur to sulfite could be enabled by APS reductase-associated electron transfer complex QmoABC and heterodisulfide reductase. The genome also contains several membrane-linked molybdopterin oxidoreductases that are thought to be involved in sulfur metabolism as subunits of thiosulfate, polysulfide, or tetrathionate reductases. Nitrate could be used as an electron acceptor and reduced to ammonium, as indicated by the presence of periplasmic nitrate and nitrite reductases. Autotrophic carbon fixation is enabled by the Wood–Ljungdahl pathway, and the complete set of genes that is required for nitrogen fixation is also present in T. dismutans. Overall, our results provide genomic insights into energy and carbon metabolism of chemolithoautotrophic sulfur-disproportionating bacterium that could be important primary producer in microbial communities of deep-sea hydrothermal vents.